Kendali Antena UAV menggunakan Kontrol PID untuk mendapatkan Gain Maksimum - Okky Nizka Pratama; Eko Setiawan; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Antenna tracker is a mechanism used to control the direction of the antenna, the system controls the horizontal servo to the right and left, while the vertical servo is up and down. The author made a tracker antenna so that it can follow a UAV that is equipped with PID control to reduce servo movement errors. In general, the system consists of UAVs for sending GPS data, GCS as data receivers, horizontal and vertical servo. PID control testing is carried out to determine the type of controller that is good for the system, disturbance testing to determine the steady state of the system, accuracy testing to determine errors in servo movement, and signal testing to determine the obtained rssi. In the PID control test, it was found that the proportional controller has the best performance with a value of 2 on the horizontal servo and 6.5 on the vertical servo. In the disturbance test, the settling time for the horizontal servo was 0.72 seconds and the vertical servo was 0.8 seconds when the disturbance was given. In the accuracy test, the average horizontal servo accuracy was 89.98% with an average error of 5.33 degrees. Meanwhile, the vertical servo obtained an average accuracy of 96.54% with an average error of 1.34. In the signal strength test, it was found that the rssi when using an antenna is better than without an antenna. At a distance of Â± 20 meters, the rsssi is -35 dbm when using an antenna and -58 dbm when not using an antenna.